PSYCHOLOGICAL MOTIVATION AS A PREDICTOR OF ATHLETIC PERFORMANCE IN BASKETBALL - Adwaa Warwar; Bashar Mohammed Ali; Nour Majid (Proximus Journal Publishing, 2025)
Sports professionals agree that basketball, like other sports, is constantly evolving. This is due to research that has helped achieve outstanding results, benefiting countries, including Iraq, at the local, regional, and global levels. There is no doubt that psychological factors are an influential factor, as they have a profound impact on athletic achievement, just like other factors (physical, skill, and tactical). Sports psychology is one of the most important foundations of the training process. Without it, it is difficult to achieve a comprehensive level of achievement, as this factor constitutes the core of the training process and is an indicator of the athletes' high abilities and potential. Motivation is one of the drivers of behavior and performance, and even the key to athletic practice. At a certain level, it can lead to satisfactory results. It works to reduce gaps and shorten distances, enhancing players' performance and promoting them to the best. Therefore, it is one of the first steps coaches must take to develop and enhance it. However, an unnatural increase or decrease in motivation below the desired level can disrupt performance and negatively impact results. Therefore, it is important to understand how to apply this condition to activate and motivate it to serve the athletic aspect. Therefore, it can be said that motivation is a double-edged sword, and it must be equal to the level of ambition
Keywords: understand; desired; motivation